CONVERSION OF FLUE GAS WASHING WATER FROM WET SCRUBBER UNITS AT THE MASARO PLASTIC REFINERY INTO ORGANIC PESTICIDES - Veradika Yemensia, Elsye
The plastic refinery is a waste management technology that processes nonbiodegradable, non-recyclable waste (residual waste) through an integrated approach combining incineration and pyrolysis, producing fuel and flue gas washing waster from the wet scrubber unit. The flue gas washing water from the Masaro plastic refinery contains compounds such as phenol, nitrate, nitrite, and ammonia that are commonly used in plant treatments, such as pesticides. This study aimed to convert the flue gas washing water into organic pesticides by adding active compounds from various plants. The experiments were conducted using three methods: heating, separate fermentation, and combined fermentation. The production process involved mixing of several plants, including bintaro fruit, garlic, turmeric, chili, lemongrass, mahogany seeds, bitter leaves, neem leaves, soursop leaves, and tobacco. The analysis was conducted to characterize the composition of the resulting pesticides and evaluate the conditions of various processing methods. The results showed that all sample variations tested positive for alkaloids, tannins, saponins, and steroids. HPLC testing of sample RT-1 revealed that the pesticide product contained active compounds such as piperine (0.175 mg/g) and quercetin (0.0147 mg/g). Further analysis using LCHRMS identified 78 compounds in the RT-1 sample, with gingerol being the most dominant compound, having a relative abundance of 48.85%. Gingerol is recognized for its antimicrobial and antioxidant properties, potentially enhancing the pesticide's effectiveness against pests and pathogens. Overall, this study demonstrates that wet scrubber flue gas washing water from a plastic refinery can be converted into effective organic pesticides, with various active compounds contributing to the biological activity of the final product.